2020
DOI: 10.1111/cts.12914
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability, Feasibility, and Utility of Integrating Pharmacogenetic Testing into a Child Psychiatry Clinic

Abstract: Pharmacogenetic (PGx) testing is a tool to identify patients at a higher risk of adverse events or treatment failure. The concern for unwanted side effects can limit medication adherence, particularly in children and adolescents. We conducted a pragmatic study to evaluate the acceptability and feasibility and gather pilot data on the utility of PGx testing in a child and adolescent psychiatry clinic. Both physicians and families participated in the study and answered pre‐survey and post‐survey questionnaires t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Despite our increasing understanding of depression pathophysiology, clinicians are unable to use biomarkers in blood or cerebrospinal fluid, neuroimaging or genomics to diagnose and guide treatment for MDD 203 . Recent studies suggest that blood levels of sertraline, a common first-line antidepressant, can successfully be predicted through analysis of genes involved in sertraline metabolism and thus, giving an indication of drug effectiveness 204 - 206 . Similarly, blood testing has identified genes (e.g., NRG1 which is involved in regulation of proliferation, survival, and differentiation of many cell types including neurons and epithelial cells 207 ), proteins (e.g.…”
Section: Treatment Induced Neuroplasticitymentioning
confidence: 99%
“…Despite our increasing understanding of depression pathophysiology, clinicians are unable to use biomarkers in blood or cerebrospinal fluid, neuroimaging or genomics to diagnose and guide treatment for MDD 203 . Recent studies suggest that blood levels of sertraline, a common first-line antidepressant, can successfully be predicted through analysis of genes involved in sertraline metabolism and thus, giving an indication of drug effectiveness 204 - 206 . Similarly, blood testing has identified genes (e.g., NRG1 which is involved in regulation of proliferation, survival, and differentiation of many cell types including neurons and epithelial cells 207 ), proteins (e.g.…”
Section: Treatment Induced Neuroplasticitymentioning
confidence: 99%
“…In a recent study 57 assessing the acceptability, feasibility, and utility of integrating pharmacogenetic testing in a child psychiatry clinic, Claudio-Campos et al found that pharmacogenomic testing was feasible and well accepted by both providers and families of children with depression and anxiety. Initial concerns from families centered on the social and ethical implications of genetic testing.…”
Section: Pharmacogenomicsmentioning
confidence: 99%
“…3 Tertiary pediatric institutions that use pharmacogenetic testing routinely have published on their experiences, which vary from automated testing of specific gene-drug pairs for all pediatric inpatients to specific units or specific testing of patients with specific diagnoses. [4][5][6][7][8][9][10][11][12][13][14][15] Despite the increasing evidence of the association of pharmacogenetic testing with benefits among pediatric patients, common implementation barriers include cost, local testing availability, and testing platform selection. 3 The decision to invest in pharmacogenetic testing implementation could be guided by better data on which drugs with the highest level of evidence for pharmacogenetic-guided dosing are most frequently prescribed or dispensed, the most frequently implicated genes that are known to influence medication dosing, and in which subpopulations these drugs are prescribed.…”
Section: Introductionmentioning
confidence: 99%